Patient Involvement in the Health Technology Assessment Process in Taiwan - Chen, Kuei An; Huang, Li Ying; Gau, Churn Shiouh (Frontiers in Medical Technology, 2022)
The COVID-19 pandemic initially had a smaller impact on Taiwan than on most other industrialized countries. However, an outbreak in late April 2021 led to a sharp surge in cases from mid-May 2021. Patient involvement in the health technology assessment (HTA) process, however, was not much affected by this; virtual meetings were implemented. This descriptive paper presents an overview of patient involvement in the HTA process in Taiwan via the National Health Insurance Administration (NHIA) online submission platform, participation in appraisal committees, education programs, and cooperation with patients' organizations, and outlines its progress and challenges. The National Health Insurance Act, amended in 2013, protects patients' rights and invites them to voice their opinions, which are then presented to the relevant authority. Based on this act, various mechanisms have been developed to involve patients, caregivers, and patient organizations in both the HTA and the reimbursement process. Prior to the Pharmaceutical Benefit and Reimbursement Scheme (PBRS) Joint Committee meeting, the NHIA built an online platform that allows patients to submit their opinions, which are then incorporated into the HTA reports. The results are also discussed with patient representatives, following which the related documents are published on the NHIA website. From May 2015 to December 2020, 30 patients' insights were published before the PBRS Joint Committee meetings. Of these, 19 (63%) were related to oncology cases. In Taiwan, approaches to fostering patient engagement include the use of a platform for patients' and patients groups' input, among others. Although patient engagement is important for understanding the needs of the target patient population, challenges in ensuring timely patient engagement and provision of relevant resources remain. In addition, further efforts are needed to implement and improve the visibility of patient input in the HTA process.